The humanin peptide mediates ELP nanoassembly and protects human retinal pigment epithelial cells from oxidative stress - Li, Zhe (Nanomedicine, 2019)
Humanin (HN) is a hydrophobic 24-amino acid peptide derived from mitochondrial DNA that modulates cellular responses to oxidative stress and protects human retinal pigment epithelium (RPE) cells from apoptosis. To solubilize HN, this report describes two genetically-encoded fusions between HN and elastin-like polypeptides (ELP). ELPs provide steric stabilization and/or thermo-responsive phase separation. Fusions were designed to either remain soluble or phase separate at the physiological temperature of the retina. Interestingly, the soluble fusion assembles stable colloids with a hydrodynamic radius of 39.1 nm at 37 °C. As intended, the thermo-responsive fusion forms large coacervates (> 1,000 nm) at 37 °C. Both fusions bind human RPE cells and protect against oxidative stress-induction of apoptosis (TUNEL, caspase-3 activation). Their activity is mediated through STAT3; furthermore, STAT3 inhibition eliminates their protection. These findings suggest that HN polypeptides may facilitate cellular delivery of biodegradable nanoparticles with potential protection against age-related diseases, including macular degeneration.